In vivo evaluation of combination therapy targeting the isoprenoid biosynthetic pathway. (May 2021) - Haney, Staci L.; Varney, Michelle L.; Chhonker, Yashpal; Talmon, Geoffrey; Smith, Lynette M.; Murry, Daryl J.; Holstein, Sarah A.
Abstract: Geranylgeranyl diphosphate synthase (GGDPS), an enzyme in the isoprenoid biosynthetic pathway (IBP), produces the isoprenoid (geranylgeranyl pyrophosphate, GGPP) used in protein geranylgeranylation reactions. Our prior studies utilizing triazole bisphosphonate-based GGDPS inhibitors (GGSIs) have revealed that these agents represent a novel strategy by which to induce cancer cell death, including multiple myeloma and pancreatic cancer. Statins inhibit the rate-limiting enzyme in the IBP and potentiate the effects of GGSIs in vitro . The in vivo effects of combination therapy with statins and GGSIs have not been determined. Here we evaluated the effects of combining VSW1198, a novel GGSI, with a statin (lovastatin or pravastatin) in CD-1 mice. Twice-weekly dosing with VSW1198 at the previously established maximally tolerated dose in combination with a statin led to hepatotoxicity, while once-weekly VSW1198-based combinations were feasible. No abnormalities in kidney, spleen, brain or skeletal muscle were observed with combination therapy. Combination therapy disrupted protein geranylgeranylation in vivo . Evaluation of hepatic isoprenoid levels revealed decreased GGPP levels in the single drug groups and undetectable GGPP levels in the combination groups. Additional studies with combinations using 50% dose-reductions of either VSW1198 or lovastatin revealed minimal hepatotoxicity with expected on-target effects of diminished GGPP levels and disruption of protein geranylgeranylation. Combination statin/GGSI therapy significantly slowed tumor growth in a myeloma xenograft model. Collectively, these studies are the first to demonstrate that combination IBP inhibitor therapy alters isoprenoid levels and disrupts protein geranylgeranylation in vivo as well as slows tumor growth in a myeloma xenograft model, thus providing the framework for future clinical exploration. Graphical Abstract: ga1